A laird for the Highland lady - Tinley, Catherine (Tinley, Catherine. Lairds of the isles, 2023)
After an unexpected encounter with Eilidh MacDonald, Max Wood thinks this shockingly beautiful woman is unlike anyone he's ever met! Working to restore the Scottish estate long neglected by his family, Max is achieving more than he thought possible. As a carefree second son, he's never considered marriage--until now... But is shaking off his decadent persona enough to win the flame-haired lady who's captured his heart?